Changes in the Rate of Lipid Peroxidation in Plasma and Selected Blood Antioxidants before and during Pregnancy in Ewes - Erisir, Mine; Benzer, Fulya; Kandemir, Fatih M. (Veterinarni A Farmaceuticka Univerzita Brno, 2009)
Pregnancy is a condition that favours oxidative stress. The aim of this study was to evaluate the oxidant and antioxidant status by measuring glutathione peroxidase (GSH-Px), catalase (CAT) activities and malondialdehyde (MDA) and glutathione (GSH) concentrations before and during pregnancy in ewes. Twelve healthy female and two healthy male Awassi sheep, aged 4-5 years, weighing approximately 50-55 kg each, were used in the study. The ewes' blood samples were taken before synchronization and during pregnancy (on 25(th) days of each month of pregnancy). Plasma MDA concentrations in the 2(nd) and 3(rd) months of pregnancy in ewes were lower than in the 1(st), 4(th), 5(th) months of pregnancy and in the non-pregnant ewes. GSH concentrations and GSH-Px activities during pregnancy were increased (P < 0.01). GSH concentrations and GSH-Px activities were the highest in the 2(nd) and 3(rd) months of pregnancy. CAT activities were decreased after the 1(st) month of pregnancy in ewes (P < 0.001). They were the lowest in the 2(nd) and 3(rd) months of pregnancy. The findings of our study show decreased CAT activities and elevated GSH concentrations and GSH-Px activities after the 1(st) month of pregnancy in ewes. These changes in the indicators under study may indicate a predisposition to oxidative stress in the 2(nd) and 3(rd) month of pregnancy in ewes.
Keywords: Awassi sheep; pregnancy; oxidant and antioxidant status